Perceptions of the Declining Fertility Rate and Evolving Views on Motherhood: A Comparative Study among University Students in India and Sri Lanka - Keshani Munasinghaghe; Sely Liyanage; Sushanthi Marudiah; Iresha M. Lakshman; Yasir Ashraf (European Scientific Journal, ESJ, 2025)
This study examines the perceptions of declining fertility rates and evolving views on motherhood among female undergraduates in Sri Lanka and India, with a focus on disciplinary and cultural variations. A mixed-methods approach was employed; the research combined a survey of 300 students from the University of Colombo and 234 students from the Vellalar Educational Trust (VET) Institute of Arts and Science in Tamil Nadu with qualitative data from 20 in-depth interviews and two focus group discussions. The findings indicate that students in both countries express moderate to high concern about fertility decline, with Indian students expressing slightly higher concern overall. In Sri Lanka, concern levels varied significantly by academic discipline, with Arts students showing greater awareness than their Science counterparts. Across both countries, delayed motherhood was primarily associated with higher education, career priorities, financial insecurity, and shifting societal norms. Nevertheless, cultural expectations continued to influence preferred childbearing ages of 25–30 years and the ideal family size of two children. These findings suggest a gradual shift towards more individualistic and diverse reproductive attitudes, while traditional values remain deeply embedded. The study contributes to a deeper understanding of how generational perspectives on fertility and motherhood are shaped by the intersection of personal aspirations, academic environment, and socio-cultural context in both countries.